A novel paradigm to assess storage of sources in memory: the source recognition test with reinstatement. Issue 4 (21st April 2021) - Symeonidou, Nikoletta; Kuhlmann, Beatrice G.
ABSTRACT: The present research aimed to devise a test of source recognition that facilitates access to source information stored in memory. Therefore, we extended the standard source-monitoring paradigm, in which items are presented in a source-neutral manner during test, by a second, subsequent test with source reinstatement. In this second test, items (i.e., words) were presented with both study sources (i.e., two speakers) consecutively such that for originally studied words, one test presentation was the exact reinstatement of the original source. To validate our assumption that the test with reinstatement primarily assesses source storage, we manipulated source storage by varying encoding frequency between-participants (repetition vs. no repetition of each item-source-pair). Additionally, we varied source similarity between-participants (similar vs. dissimilar speakers). Data analyses ( N  = 146) based on multinomial and signal detection models showed a source memory enhancement in the second test with reinstatement compared to the first standard test, especially for similar sources. Additionally, repetition selectively benefited source memory in the second test, validating our interpretation of the second test as a measure for source storage. Altogether, our novel source recognition test offers a promising method for investigating various well-known source memory phenomena more comprehensively.